Are General Intelligence and Implicit Memory Related?: The Effect of Age - Hande Kaynak (Hacettepe Üniversitesi Edebiyat Fakültesi Dergisi, 2019)
This study investigated the relationship between general intelligence and implicit memory performance in conjunction with aging. Data have been collected from 95 volunteers (49 young-46 older adults). General intelligence was measured by the Raven Standard Progressive Matrices (RSPM) test. Participants’ implicit memory performance was measured by the Word Stem Completion (WSC) task, in which the participants were presented with first three letters of a word and asked to complete this stem with the first word that comes to their mind. Explicit memory performance was also measured to be able to make a comparison with implicit memory performance and to document the differentiation between implicit and explicit memory. Although the same WSC task was used to measure implicit and explicit memory performance separately, the different instructions were used to deduce the different memory types. According to the results of factorial ANOVA, the main effect of age on general intelligence score was found to be statistically significant. After running further analyses by Pearson product-moment correlation coefficients, results indicated that RSPM test total correct score had a tendency to decrease with increasing age and RSPM test completion time had a tendency to increase with aging. Results also showed that implicit WSC task score and RSPM test total correct score were positively correlated. Similarly, explicit WSC task score and RSPM test total correct score were positively correlated, too. However, RSPM test completion time did not differ depending on implicit and explicit memory performances which were measured by WSC task. The present study indicated the relation between implicit WSC task and general intelligence. Within this context, this study is important to draw attention to the contribution of implicit memory measurement which is in the shadow of traditional explicit memory measurements to general intelligence, especially in older population.